2020
DOI: 10.1016/j.nmni.2020.100743
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between blood group and risk of infection and death in COVID-19: a live meta-analysis

Abstract: The relationship between ABO blood group and the incidence of coronavirus disease 2019 (COVID-19) infection and death has been investigated in several studies. The reported results were controversial, so the objective of the present study was to assess the relationship between different blood groups and the onset and mortality of COVID-19 infection using a meta-analysis method. We searched relevant databases using appropriate MeSH terms. We screened articles on the bases of titles, abstracts and full text, and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
1
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 28 publications
3
55
1
10
Order By: Relevance
“…Thus, ORs for blood group O ranged from 0.53 to 0.9 and ORs for non-O blood groups ranged from 1.12 to 3.7. Meta-analyses of the earliest available data have already been conducted, confirming the effect [ 88 , 89 , 90 , 91 , 92 ].…”
Section: Studies Linking Abo Blood Types To Covid-19mentioning
confidence: 77%
“…Thus, ORs for blood group O ranged from 0.53 to 0.9 and ORs for non-O blood groups ranged from 1.12 to 3.7. Meta-analyses of the earliest available data have already been conducted, confirming the effect [ 88 , 89 , 90 , 91 , 92 ].…”
Section: Studies Linking Abo Blood Types To Covid-19mentioning
confidence: 77%
“…The results are inconsistent. However, it seems that the risk of COVID-19 is positively associated with A blood group compared with O phenotype [ 17 , 18 , 24 , 26 , 28 ]. Our present finding, confirmed the relationship of ABO genetic system with susceptibility to COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, no association between ABO blood groups and COVID-19 was found in French and Spanish patients [8,13]. However, in a meta-analysis study, it was emphasized that individuals of group A are at greater risk of developing COVID-19 while those of group O were at lower risk [11]. Further meta-analysis suggested that individuals of group A may be more susceptible to COVID-19, while individuals of group O may have a lower risk of developing the disease.…”
Section: Allele Frequencies Of Abo Blood Groupsmentioning
confidence: 95%
“…Some biological determinants of the host have also been considered as prominent markers associated with susceptibility to COVID-19. Among these determinants, ABO blood groups have recently been introduced as important predisposing factors in the development of infection [7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%